Standardized Swallowing Assessment (SSA) Diagnostic Test for Diysphagia Screening in Stroke Patients in the Stroke Center Treatment Room - Nurun Salaman Alhidayat; Rizki Nugraha Agung; Ninik Yunitri (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stroke is the second leading cause of death in the world with cases continuing to increase every year, and one of the complications that often occurs is dysphagia, which can cause nutritional and respiratory disorders. Early detection of dysphagia through appropriate screening, such as the Standardized Swallowing Assessment (SSA), is very important to prevent further complications and improve the recovery of stroke patients.. Objective: to conduct diagnostic tests of the SSA assessment instrument for dysphagia screening in the Stroke Center room of Labuang Baji Hospital, South Sulawesi Province, Makassar. Method: In this study, a diagnostic test was used by measuring the sensitivity and specificity of the SSA instrument. The diagnostic test is a descriptive observational study with a cross-sectional study design. Results: The results of this study indicate that the sensitivity level of the SSA instrument reached 96.55% and the specificity level of the SSA instrument reached 87.5%. Conclusions: Dysphagia screening Standardized Swallowing Assessment (SSA) can be used as a standard instrument to identify dysphagia manifestations.